2022
DOI: 10.1002/tqem.21904
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of phosphate solubilizing fungus from rice fields of Odisha for agro‐ecological sustainable agriculture

Abstract: Phosphorus (P), the second most essential nutrient, plays a remarkable role in energy transfer, storage, plant growth, and development. It is the least mobile and accessible to plants in most soil conditions as compared to the other key nutrients. Phosphate‐solubilizing fungus (PSF) plays a vital role in supplying phosphorous to plants from the soil. Hence this research intends to assess the phosphorous and nutritional status of collected soil samples as well as isolation of potential fungal strains. Twelve so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Djuuna et al [21] found correlations between the number of PSF and the levels of soil P availability and moisture content, indicating an increase in soil P availability with a greater abundance of PSF in the soil. Some strains of filamentous fungi have been studied in research involving species of the genera Alternaria [22,23], Aspergillus [24], Eupenicillium [25], Fusarium [26], Cladosporium [27], Gongronella [28] Helminthosporium [29], Mortierella [30] Rhizopus [22], Talaromyces [28,31], and Trichoderma [32], prominent among which are the Aspergillus y Penicillium [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Djuuna et al [21] found correlations between the number of PSF and the levels of soil P availability and moisture content, indicating an increase in soil P availability with a greater abundance of PSF in the soil. Some strains of filamentous fungi have been studied in research involving species of the genera Alternaria [22,23], Aspergillus [24], Eupenicillium [25], Fusarium [26], Cladosporium [27], Gongronella [28] Helminthosporium [29], Mortierella [30] Rhizopus [22], Talaromyces [28,31], and Trichoderma [32], prominent among which are the Aspergillus y Penicillium [32,33].…”
Section: Discussionmentioning
confidence: 99%